Usefulness of cardiac resynchronisation therapy devices and implantable cardioverter defibrillators in the treatment of heart failure due to severe systolic dysfunction: systematic review of clinical trials and network meta-analysis. Issue 1 (27th January 2016) - García García, M A; Rosero Arenas, M A; Ruiz Granell, R; Chorro Gascó, F J; Martínez Cornejo, A
Abstract : Aim: To assess the effectiveness of cardiac resynchronisation therapy (CRT), implantable cardioverter defibrillator (ICD) therapy, and the combination of these devices (CRT+ICD) in adult patients with left ventricular dysfunction and symptomatic heart failure. Methods: A comprehensive systematic review of randomised clinical trials was conducted. Several electronic databases (PubMed, Embase, Ovid, Cochrane, ClinicalTrials.gov) were reviewed. The mortality rates between treatments were compared. A network was established comparing the various options, and direct, indirect and mixed comparisons were made using multivariate meta-regression. The degree of clinical and statistical homogeneity was assessed. Results: 43 trials involving 13 017 patients were reviewed. Resynchronisation therapy, defibrillators, and combined devices (CRT+ICD) are clearly beneficial compared to optimal medical treatment, showing clear benefit in all of these cases. In a theoretical order of efficiency, the first option is combined therapy (CRT+ICD), the second is CRT, and the third is defibrillator implantation (ICD). Given the observational nature of these comparisons, and the importance of the overlapping CIs, we cannot state that the combined option (CRT+ICD) offers superior survival benefit compared to the other two options. Conclusions: The combined option of CRT+ICD seems to be better than the option of CRT alone, although no clear improvement in survival was found for the combined option. It would be advisable to perform a direct comparative study of these two options.